Context Analysis of Teachers’ Learning Design Practice Through Activity Theory, Distributed Cognition, and Situated Cognition - Queiros, Leandro Marques (2021)
The objective of this work was to analyze how different theoretical frameworks encompass the teachers’ learning design practice. We compared the use of Activity Theory, Distributed Cognition, and Situated Cognition theoretical frameworks to deal with data analysis and interpretations and compared them. The Activity Theory is useful to study technology in activities since the unit of analysis is an activity, and it is always instrumentally mediated. The use of Distributed Cognition framework lies in exploring how mental schemas of the mind can represent structures outside the mind. Finally, Situated Cognition is focused on analyzing the continuous relationship integrating teachers and environmental instruments to act on class planning to understand the flow of the activities involved in this real scenario. The analysis from different theoretical points of view gave the designers a better understanding of the activity structure, how the artifacts support distributed cognitive activities and finally how the artifact is embodied in the planning activities. The present work aims to have contributed to a better understanding of teachers’ planning practices to influence the design of lessons planning software services to be integrated into teaching practice.